2013
DOI: 10.5812/jjm.11250
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Keratinophilic Fungi and Aerobic Actinomycetes From Park Soils in Gorgan, North of Iran

Abstract: Background: Keratinophilic fungi are a group of fungi that colonize in various keratinous substrates and degrade them to the components with low molecular weight. This study was conducted to determine the prevalence of keratinophilic fungi and aerobic Actinomycetes in soil of city parks in Gorgan. Objectives: In this study, we surveyed the city park soils of Gorgan (a northern province of Iran) to determine the identities and diversity of soil aerobic Actinomycetes, keratinophilic and non-keratinophilic fungi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…The hair baiting technique was first used to isolate keratinophilic fungi from the soil by Vanbreuseghem ( 34 ) and has become applied widely. So far, the investigation of such resources is still dominated by traditional isolated cultures and baiting with materials of human or animal origin, such as feathers ( 35 ), horsehair ( 4 ), wool ( 36 ), human hair ( 37 ), and human nails ( 38 ). Only a small number of studies have used next-generation sequencing technologies ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hair baiting technique was first used to isolate keratinophilic fungi from the soil by Vanbreuseghem ( 34 ) and has become applied widely. So far, the investigation of such resources is still dominated by traditional isolated cultures and baiting with materials of human or animal origin, such as feathers ( 35 ), horsehair ( 4 ), wool ( 36 ), human hair ( 37 ), and human nails ( 38 ). Only a small number of studies have used next-generation sequencing technologies ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Malek et al . [ 34 ] isolated 17 different fungal genera from the soil of parks in Gorgan, Iran. Overall, 36% of the isolates were related to Zygomycetes , and the genus Mucor was the most frequent isolate among other Zygomycetes genera.…”
Section: Discussionmentioning
confidence: 99%
“…In this present study Aspergillus spp., spp., Absidia spp., Cladosporium Penicillum spp. were the most frequently isolated non-dermatophytic mold in this study; this is not surprising as these molds have been reported to be highly ubiquitous in nature 30,31,32,33]. A number of skin infections in man and animal has also been linked to them especially in immunocompromised host and onychomycosis [34,35,36,37].…”
Section: Resultsmentioning
confidence: 59%